2002
DOI: 10.1021/op0255231
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ionic Liquids to Increase the Yield and Enzyme Stability in the β-Galactosidase Catalysed Synthesis of N-Acetyllactosamine

Abstract: The use of ionic liquids as alternative solvents for enzyme catalysis was investigated. β-Galactosidase from Bacillus circulans catalyses the synthesis of N-acetyllactosamine starting from lactose and N-acetylglucosamine in a transglycoslyation reaction. The addition of 25% v/v of 1,3-di-methyl-imidazol-methyl sulfate [MMIM] [MeSO4] as a water-miscible ionic liquid suppresses the secondary hydrolysis of the formed product, resulting in doubling the yield to almost 60%. The enzyme can be reused several times af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
114
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(120 citation statements)
references
References 50 publications
5
114
0
1
Order By: Relevance
“…Following the stimulating work of Kaftzik et al (2002) on b-galactosidase-catalyzed synthesis of N-acetyl-lactosamine in ionic liquids, this is the first report in which the influence of a water-miscible ionic liquid cosolvent on the transglycosylation properties of a glycosidase is described in some detail. The results show that the transferase activity of CelB can be improved significantly by addition of the widely used ionic liquid [MMIm] [MeSO 4 ].…”
Section: Discussionmentioning
confidence: 97%
“…Following the stimulating work of Kaftzik et al (2002) on b-galactosidase-catalyzed synthesis of N-acetyl-lactosamine in ionic liquids, this is the first report in which the influence of a water-miscible ionic liquid cosolvent on the transglycosylation properties of a glycosidase is described in some detail. The results show that the transferase activity of CelB can be improved significantly by addition of the widely used ionic liquid [MMIm] [MeSO 4 ].…”
Section: Discussionmentioning
confidence: 97%
“…It was shown that the enzyme activity of β-galactosidase could be vastly increased in an IL environment. 93 Preliminary studies of our lab have demonstrated that β-galactosidase was active when BGs were re-suspended in the IL [Bmim]PF 6 .…”
mentioning
confidence: 99%
“…The first reaction was carried out at 40 C in 100 mM phosphate buffer at pH 6.5, supplemented with MgCl 2 (10 mM), starting from lactose 2 (1 M) as a galactosyl donor and from GlcNAc 1 (250 mM) as the acceptor (Scheme 1). Various galactosylated derivatives of GlcNAc were found in the media after 5 h of reaction catalyzed by KlbGal (1,014 U mL À1 ) or BcbGal (142 U mL…”
Section: Resultsmentioning
confidence: 99%
“…Kinetics studies were performed at 40 C with a diluted solution of the crude preparation of KlbGal (1:500 dilution) or BcbGal (1:250 dilution) prepared in 100 mM phosphate buffer, pH 6.5 (10 mM MgCl 2 ), on a chromogenic substrate (o-nitrophenyl-b-D-galactopyranoside). Continuous changes in absorbance at 415 nm were monitored in spectrophotometric cuvettes of 1-cm path length using a UV-visible spectrophotometer (Lambda 650; Perkin Elmer), associated with a PTP1 (Peltier Temperature Programmer) system.…”
Section: Determination Of Enzyme Activity By Spectrophotometric Assaymentioning
confidence: 99%